2023
DOI: 10.1002/ecs2.4280
|View full text |Cite
|
Sign up to set email alerts
|

High survival following bleaching underscores the resilience of a frequently disturbed region of the Great Barrier Reef

Abstract: Natural bleaching events provide an opportunity to examine how local‐scale environmental variation influences bleaching severity and recovery. During the 2020 marine heat wave, we documented widespread and severe coral bleaching affecting 75%–98% of coral cover throughout the Keppel Islands in the southern inshore Great Barrier Reef. Acropora, Pocillopora, and Porites were the most severely affected genera, while Montipora was comparatively less susceptible. Site‐specific heat‐exposure metrics were not correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 102 publications
(201 reference statements)
0
15
0
Order By: Relevance
“…Severe bleaching occurred throughout Woppaburra sea Country (the Keppel Islands) during the 2020 marine heatwave, but mortality of Acropora millepora was low (~ 6.5% this study; Page et al 2023). Despite recovery by the time of coral spawning six months later, we found that heavily bleached colonies experienced a signi cant reduction in reproductive output in the form of depressed egg numbers, while egg size was conserved, resulting in an estimated 21% reduction in population-level fecundity.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…Severe bleaching occurred throughout Woppaburra sea Country (the Keppel Islands) during the 2020 marine heatwave, but mortality of Acropora millepora was low (~ 6.5% this study; Page et al 2023). Despite recovery by the time of coral spawning six months later, we found that heavily bleached colonies experienced a signi cant reduction in reproductive output in the form of depressed egg numbers, while egg size was conserved, resulting in an estimated 21% reduction in population-level fecundity.…”
Section: Discussionmentioning
confidence: 67%
“…Only 4.5% of colonies did not visually bleach (category = 6, n = 16). Whole-colony mortality was highest at PI (17%, n = 16) while no whole-colony mortality was observed at NKI (SI Table 1, Page et al 2023). The likelihood of survival signi cantly increased as a function of bleaching score (GLM: z = 3.437, p < 0.001) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, the low cumulative heat stress experienced by those regions may result in coral assemblages that are naïve to high heat stress (Hughes et al, 2021). As such, mild but highly prevalent coral bleaching occurred in the southern GBR during 2016–2017 (21% of colonies; Kennedy et al, 2017) and 2020 (48% of colonies; Nolan et al, 2021; 86% of colonies; Page et al, 2023) and occurred under lower cumulative heat stress (DHW) than in central and northern GBR (Hughes et al, 2021). Further investigations are thus required to understand how recurrent warming disturbances and gene flow with northern regions will shape the evolution of these cooler reefs.…”
Section: Discussionmentioning
confidence: 99%
“…Our observations show that some coral holobionts can rapidly change and recover during and after successive severe disturbances. In fact, scientists have recently and repeatedly observed both devastating losses and unexpected recoveries in coral reefs after massive disturbances, such as those on both these remote Mo'orean coral reefs as well as continental reefs, such as the Great Barrier Reef (Adjeroud et al., 2018; Page et al., 2023), and microbiomes may help mediate such recoveries. This work supports the hypothesis that microbiome acclimatization, resilience, and resistance may be an additional layer of coral adaptive capacity during repeated marine heatwaves and demonstrates that some coral microbiomes may contribute to ecological memory of past disturbance through acclimatizing and developing resistance to repeated stress.…”
Section: Discussionmentioning
confidence: 99%